Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1105/tpc.10.5.673
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis bZIP Protein HY5 Directly Interacts with Light-Responsive Promoters in Mediating Light Control of Gene Expression

Abstract: The Arabidopsis HY5 gene has been defined genetically as a positive regulator of photomorphogenesis and recently has been shown to encode a basic leucine zipper type of transcription factor. Here, we report that HY5 is constitutively nuclear localized and is involved in light regulation of transcriptional activity of the promoters containing the G-box, a well-characterized light-responsive element (LRE). In vitro DNA binding studies suggested that HY5 can bind specifically to the G-box DNA sequences but not to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
224
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(238 citation statements)
references
References 30 publications
11
224
0
3
Order By: Relevance
“…As expected, we found a number of light-regulated genes that have partly been reported to be under HY5 control, e.g., chalcone synthase (CHS) genes or chlorophyll a/b binding protein (CAB) genes and other components of the photosynthetic apparatus (16 genes in total) [4,15,20,21]. Other overrepresented, annotated gene classes that are misregulated in the double mutant include many transcription factors (57 genes) as well as ubiquitin ligase components (24 genes).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…As expected, we found a number of light-regulated genes that have partly been reported to be under HY5 control, e.g., chalcone synthase (CHS) genes or chlorophyll a/b binding protein (CAB) genes and other components of the photosynthetic apparatus (16 genes in total) [4,15,20,21]. Other overrepresented, annotated gene classes that are misregulated in the double mutant include many transcription factors (57 genes) as well as ubiquitin ligase components (24 genes).…”
Section: Resultssupporting
confidence: 62%
“…In hyh, basipetal transport is normal, however, and the influence of hyh on this trait in the double mutant, if any, is marginal. Because flavonoids have been identified as regulators of basipetal auxin transport in the root [28] and because the expression of rate-limiting enzymes in flavonoid biosynthesis, notably CHS, is largely HY5 dependent [15,20,21], we investigated whether hy5 root agravitropism is a secondary consequence of decreased flavonoid biosynthesis. To test this hypothesis, we fed hy5 seedlings with naringenin, thus bypassing the requirement for CHS expression.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that combinations of different LREs, rather than individual elements, confer proper light-responsiveness to a promoter (Puente et al, 1996). The GATA element functions together with the G-box or GT1 motifs to confer normal response to a wide spectrum of light signals involving multiple photoreceptors and the COP/DET/FUS complex (Chattopadhyay et al, 1998a). These results indicated a role of the GATA element as an essential partner with other LREs in light-regulated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In petunia, sequences corresponding to Arabidopsis transcription factors involved in light signaling are more divergent (Table S2). Currently, transcripts exhibiting significant sequence conservation to the phy-A specific signaling partner FHY1 (Desnos et al 2001), the bZIB transcription factor HY5/HYH family (Chattopadhyay et al 1998), the kinase substrate PKS1 family (Fankhauser et al 1999), the EXS and SPX domain blue-light signaling partner SHB1 (Kang and Ni 2006) and the Ca +2 -binding protein SUB1 (Guo et al 2001) are absent from Petunia x hybrida databases (Fig. 1b).…”
Section: Data Mining For Photoperception Light-signaling and Anthocymentioning
confidence: 99%